An Appraisal of Gender Differential in Tertiary Education in Yobe State, Nigeria - Sanda, Yakubu Babaniyo (International Journal on Integrated Education, 2023)
The aim of this research is to appraise gender differential in the enrolment of male and female youths in tertiary institutions in Yobe State, Nigeria. The specific objectives of the research are: to find out if there is gender gap between male and female youths in Yobe State tertiary education system; to identify the socio-cultural factors that create a barrier for the enrolment of female youths in tertiary education in Yobe State; and to provide the appropriate measures to address the socio-cultural factors creating a barrier for the enrolment of female youths in tertiary education in Yobe State. The study adopts feminist approach to explain the underlying factors accounting for the marginalisation of girls and women in various societies. The study is a survey research, and the sample size of the study was 456 respondents (450 quantitative data respondents and 6 qualitative data respondents). Cluster and purposive sampling techniques were adopted. Both primary and secondary data were used, with questionnaire and in-depth interview (IDI) as data instruments. The data was analysed using mixed method. The gender gap in tertiary education manifests through female youths not having opportunity for enrolment; female youths not given admissions; more male students in the schools; parent’s ignorance of the importance of female child’s education and misconstrued understanding of the religious ruling on females’ education, etc. Factors responsible for gender gap in education in the State include: some parents not permitting daughters to proceed to tertiary education; husbands not permitting wives to proceed to tertiary education; and some men being sceptical of marrying ladies who attended tertiary institutions. The measures for addressing socio-cultural factors creating gender barrier in tertiary education include: free education for females at the tertiary level by the government; more awareness on female education at the tertiary level; Muslim scholars to encourage females into higher institutions; address cultural barriers to gender gap in tertiary education; and introducing women empowerment programmes. The study recommended that to address gender barrier in Yobe State tertiary education there should be: free education for females at the tertiary level by the government; more awareness creation on female education at the tertiary level; encouragement to men to allow wives enroll in tertiary education, etc.